DESIGN TOOL ROOM TEMPERATURE MEASUREMENT WITH TEMPERATURE SENSOR USING LM35 AT89S51 MICROCONTROLLER - Syarip Hidayattullah; Nenny Anggraini, SKom., MT (Jurnal Sistem Informasi, 2009)
In writing that I make with the title "Room Temperature Measuring EquipmentDesign With LM35 Temperature Sensor Using AT89S51 MICROCONTROLLER "about design for temperature data acquisition system that uses the basic componentsof an ADC, temperature sensor, microcontroller AT89S51 and Seven Segment as aviewer facility. Temperature data acquisition system into something that is veryimportant in industrial activity, because it is a small part of a process control. Withregard to the importance of the system, hence the temperature data acquisition systemdesign that is capable of temperature monitoring activity of a plant. The data to bemeasured is a physical property so as to be processed temparature and displayed inthe form of electrical systems used LM35 temperature sensor that is able to convertthese quantities with increasing 10mV/oC.To be able to design the system was first carried out the process of cha nging thetemperature into an analog voltage using a LM35 temperature sensor. after goingthrough the process was strengthened by the signal conditioning, analog voltageconverted into digital data using the ADC 0804. Digital data obtained is thenprocessed by the Microcontroller AT89S51 and displayed, so we get someinformation about OC units of the plant temperature on a Seven Segment of thetemperature data acquisition system design is obtained that this system has the abilityto measure the temperature from 25oC to 100oC with average errors Averagetemperatures for the appointment of 0.266 oC.